2011
DOI: 10.1002/ange.201007775
|View full text |Cite
|
Sign up to set email alerts
|

Solid‐State NMR Spectroscopic Analysis of the Ca2+‐Dependent Mannose Binding of Pradimicin A

Abstract: Erleichterte Analyse: Das Ca2+‐abhängige Binden des nichtpeptidischen Kohlenhydratbinders Pradimicin A (PRM‐A) durch Mannose (Man) wurde im Festkörper an PRM‐A‐Aggregaten untersucht, was mit dem Dreikomponentengleichgewicht verknüpfte Probleme beseitigte. 113Cd‐NMR‐Spektroskopie und dipolgestützte zweidimensionale Rotationsresonanz ergaben die Mannosebindungsstelle von PRM‐A und die entscheidende Rolle des Ca2+‐Ions (siehe Bindungsmodell).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…[19] Regarding the interaction with Ca 2 + ions, our previous study suggested the possibility that PRM-A binds Man in a Ca 2 + -mediated manner through its carboxylate group. [14] Unfortunately, lack of data regarding the geometry of Ca 2 + coordination prevented us from conducting further calculations in the presence of Ca 2 + ions to estimate the true mode of binding. However, it can be hypothesized that Man coordinates Ca 2 + ions through the 4-hydroxyl group, which is in the proximity of the carboxylate group of PRM-A in our binding model.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[19] Regarding the interaction with Ca 2 + ions, our previous study suggested the possibility that PRM-A binds Man in a Ca 2 + -mediated manner through its carboxylate group. [14] Unfortunately, lack of data regarding the geometry of Ca 2 + coordination prevented us from conducting further calculations in the presence of Ca 2 + ions to estimate the true mode of binding. However, it can be hypothesized that Man coordinates Ca 2 + ions through the 4-hydroxyl group, which is in the proximity of the carboxylate group of PRM-A in our binding model.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the H2 proton of Man lies over the A ring of PRM‐A at a distance of 3.03 Å, implying that the CH/π interaction between them could also contribute to stabilization of the complex as observed in many carbohydrate–receptor systems 19. Regarding the interaction with Ca 2+ ions, our previous study suggested the possibility that PRM‐A binds Man in a Ca 2+ ‐mediated manner through its carboxylate group 14. Unfortunately, lack of data regarding the geometry of Ca 2+ coordination prevented us from conducting further calculations in the presence of Ca 2+ ions to estimate the true mode of binding.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our initial attempt to explore this issue was made by solid-state 113 Cd-NMR investigation using 113 Cd 2D with a spin of 1/2 as a surrogate probe for Ca 2D with a spin of 7/2. 34) Based on the previous report that PRMs bound Man in the presence of Cd 2D , 27) the [PRM-A 2 / 113 Cd 2D ] complex was prepared as aggregates, and subjected to solid-state 113 Cd-NMR analysis. Although the chemical shift of the 113 Cd signal in the 1D spectrum of the complex gave no information regarding the geometric arrangement of 113 Cd 2D coordination, subsequent rotational-echo double resonance (REDOR) and 111 Cd frequency-selective REDOR (FSR) experiments using the 111 Cd 2D probe gave an unexpected result.…”
Section: Estimation Of the [Prm 2 /Ca 2d /Man 2 ] Complexmentioning
confidence: 99%